Combination of Spiritual Benson Relaxation and Lavender Aromatherapy (SBR-LA) on Anxiety, Sleep Quality and Blood Pressure in Hypertension Patients - Muhammad Basuni; Eppy Setiyowati; Chilyatiz Zahroh (Universitas STRADA Indonesia, 2025)
Background: A person's anxiety due to an illness is one of the causes of hypertension or an increase in blood pressure above the normal limit in all age groups. Hypertension that is not recognized and is not treated immediately can cause various kinds of comorbidities. Therefore, apart from pharmacological treatment, non-pharmacological therapy is also needed to reduce anxiety and blood pressure and improve the quality of sleep for hypertension sufferers. Purpose: The aim of this research is Explain the influence of Combination Of Spiritual Benson Relaxation and Lavender Aromatherapy (SBR-LA) on anxiety, sleep quality and blood pressure in hypertension patients. Methods: This research is quantitative research that uses a quasi-experiment research design with a pretest - posttest control group design approach. The entire population of hypertension patients in TNI AL Dr.Oepomo Hospital many as 97 people. The sample size was 44 respondents. The sampling technique is purposive sampling. The research independent variables are: Combination Of Spiritual Benson Relaxation And Lavender Aromatherapy (SBR-LA) and the dependent variables are anxiety, sleep quality and blood pressure. Analysis used the paired t-test with a significant p value <0.05. Results: The results of research using the paired t-test show that there is an effect of giving The Effect of the Combination of Spiritual Benson Relaxation and Lavender Aromatherapy (SBR-LA)which is significant for anxiety with p value = 0.000, sleep quality with p value = 0.000 and systolic blood pressure p value = 0.000, diastolic blood pressure p value = 0.000. Conclusion: The Effect of the Combination of Spiritual Benson Relaxation and Lavender Aromatherapy (SBR-LA) Effectively reduces anxiety levels, improves sleep quality and lowers blood pressure in hypertension patients. This technique is very easy to do, so it can be applied as a nursing intervention in inpatient rooms to develop nursing knowledge in hospitals.